Study on preparation and performance of a thermosetting polyurethane modified asphalt binder for bridge deck pavements. (4th April 2022) - Yang, Fan; Cong, Lin; Li, Zhaolin; Yuan, Junjie; Guo, Guihong; Tan, Le
Highlights: The curing temperature and time of a newly developed thermosetting polyurethane modified asphalt binder were studied in the laboratory. Polyurethane resin formed a continuous polymeric network in asphalt binder when resin content exceeds 30 wt%. The thermosetting polyurethane modified asphalt binder had shown an outstanding high-temperature deformation resistance and low-temperature elongation-to-break capacity. Abstract: With the rapid development of traffic volume and loading, sustainable pavement materials are developing to improve the longevity of orthotropic bridge deck pavement structures. This paper aims to develop a new flexible binder with improved mechanical characteristics for bridge deck applications. This research studied the preparation process, microstructural morphology, and mechanical properties of a newly developed thermosetting polyurethane modified asphalt binder (TPUA). The results showed that the viscosity of TPUA was greatly affected by the preparation temperature and the viscosity growth rate increased with the increase of preparation temperature. The curing time was determined by the change in the absorption peak of the infrared spectra of the NCO groups. When the content of the PU modifier exceeded 30 wt%, the polyurethane (PU) resin formed a continuous polymeric network in asphalt binder, and the PU had relatively good compatibility with the asphalt binder. TPUA still showed the characteristics of a viscoelastic material at medium and low temperatures. When the content of PU exceeded 30 wt%, TPUA gradually showed the characteristics of an elastic material at high temperature and had excellent high-temperature deformation resistance and elastic recovery properties. In addition, the TPUA binder showed improved low-temperature flexibility with the increase of PU. Overall, the mechanical properties of the asphalt binder were substantially enhanced with the incorporation of PU resin, generating a flexible binder with favorable application prospects.